Pengaruh Model Problem Based Learning Berbantuan PhET Simulasi terhadap Peningkatan Kemampuan Berpikir Kritis Fisika Peserta Didik - Jihan Sulistya Ananda; Muh. Makhrus; Sutrio; Wahyudi (Mataram University, 2026)
This study aimed to determine the effect of the Problem Based Learning (PBL) model assisted by PhET Simulasi on improving students’ critical thinking skills in physics. The study employed a quasi-experimental method using a non-equivalent control group design. The sample consisted of 33 students from Class XI IPA 2 as the experimental group and 32 students from Class XI IPA 3 as the control group at SMAN 7 Mataram during the 2025/2026 academic year. The research instrument was an essay test designed to measure critical thinking skills and had met the validity, reliability difficulty level and discrimination power requirements. Data were collected through pretests and posttests and analyzed using normality tests, homogeneity tests, independent sample t-tests, and N-Gain analysis. The results showed that the mean pretest scores of the experimental and control groups were 40.91 and 38.86, respectively, while the mean posttest scores were 85.51 and 77.82. The normality test indicated that the posttest data of both the experimental group were 3.3844 and the control group were 3.8180) were normally distributed because < were 11.070. The homogeneity test showed that the variances of both groups were homogeneous with = 1.7402 < = 1.810. The hypothesis testing using the pooled variance t-test revealed that = 3.79 > = 1.998, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. Furthermore, the N-Gain score of the experimental group was 0.755 in the high category, while that of the control group was 0.637 in the medium category. These findings indicate that the implementation of the Problem Based Learning model assisted by PhET Simulasi has a significant positive effect on improving students’ critical thinking skills in physics on wave material.